Sublethal doses of copper sulphate initiate deregulation of glial cytoskeleton, NF-kB and PARP expression in Capoeta umbla brain tissue - M. Kirici; V. S. Nedzvetsky; C. A. Agca; V. Y. Gasso (Regulatory Mechanisms in Biosystems, 2019)
Copper sulphate pentahydrate (CuSO4∙5H2O) is widely used as a pesticide not only in agricultural but in aquaculture farming as well. Copper sulphate is a cheap chemical and able to contaminate the environment, especially water sources, which is crucial for fish harvesting and farming. The copper contamination in some areas is caused over decades because this pesticide has long been used everywhere. Copper ions inhibit invasive aquatic plants and many microorganisms but contaminate soil and natural water resources. The family of copper-containing chemicals is frequently used as algaecides in swimming pools. Despite the high toxicity of copper ions for fish in freshwater ponds, copper sulphate remains one of the prevalent pesticides in fish farming everywhere. High cytotoxicity and accumulation of the copper ions in sediments require study and calculation of the optimal dosage for its use as an antiseptic agent which will not have a detrimental effect on various tissue types of aquatic organisms. The main recognized mechanism which accompanies the toxic effect of copper ions is the generation of oxidative stress. Neural tissue cells are extremely susceptible to oxidative damage and the functions of the CNS are critical to the vitality of organisms. Glial cells maintain the structure and many vital functions of neurons. The cytoskeleton glial fibrillary acidic protein (GFAP), transcriptional nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) and Poly(ADP-ribose) polymerase (PARP) are critical participants in a cellular response to a toxic agent impact. As this takes place, it could be applied in biomarking of heavy metal toxicity. In the presented study, we investigated the effects of copper ions on PARP, NF-kB, and GFAP expression in the Tigris scraper Capoeta umbla brain tissue. For 96 hours the fish were exposed to copper sulphate at sublethal concentrations, namely 1/2, 1/4 and 1/8 of the LD50 value. Western blot analysis of GFAP and PARP was used to assess further effects in the brain tissue. Every studied dose of copper significantly downregulated the expression of GFAP after 72 hours of treatment. In spite of the common increment in the GFAP content, 48 hours exposure to copper initiated the upregulation of that cytoskeleton marker. Moreover, treatment with copper sulphate induced several changes in the β-actin level, especially in the fish group treated for 72 hours. The observed effect of copper in the fish brain evidences the unspecific toxic effect of the copper ions in the brain tissue cells. The obtained results demonstrated meaningful disturbance in the expression of transcriptional factor NF-kB in the brain of the fish group exposed to copper. The changes found in the fish brain indicate the dose-dependent effect in a concentration range 185–740 µg/L of copper sulphate during 72 hours. However, the exposure to low dose of copper ions showed no effect in the fish group treated for 24 hours. Comparative analyses of the PARP content in the brain of fish exposed to copper for 72 hours was significantly less than in the groups treated with copper for both 24 and 48 hours. Thus, the copper ions in the dose range 185–740 µg/L can suppress PARP expression in a time-dependent manner. The results showed that copper ions could induce astroglial response accompanied by modulations of NF-kB and PARP-1 expression. The data obtained in this study suggest that copper sulphate has a significant effect on astrogliosis and DNA damage in the fish brain.